2022
DOI: 10.1182/blood.2022015724
|View full text |Cite
|
Sign up to set email alerts
|

Erythroblastic islands foster granulopoiesis in parallel to terminal erythropoiesis

Abstract: The erythroblastic island (EBI), composed of a central macrophage surrounded by maturing erythroblasts, is the erythroid precursor niche. Despite numerous studies, its precise composition is still unclear. Using multispectral imaging flow cytometry (IFC), in vitro island reconstitution, and single cell RNA-sequencing (scRNA-seq) of adult mouse bone marrow EBI-component cells enriched by gradient sedimentation, we present evidence that the CD11b+-cells present in the EBIs are neutrophil precursors specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…Emerging technologies will also aid in our understanding of the erythromyeloblastic niche and associated anaemic conditions. Although scRNAseq may not be enough to appreciate the unique signature of the central macrophage, single-cell multiomics (CITE-seq) validated by biologic data have improved our understanding of these structures [20 ▪▪ ]. If the tight interaction of macrophages with other cell types in the islands limit the number or bias the populations of the central macrophages isolated for further studies, perhaps we must isolate deeper structures within the cell, such as the nucleus or mitochondria, for the unique cellular signature that is so important for understanding the EMBI [41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging technologies will also aid in our understanding of the erythromyeloblastic niche and associated anaemic conditions. Although scRNAseq may not be enough to appreciate the unique signature of the central macrophage, single-cell multiomics (CITE-seq) validated by biologic data have improved our understanding of these structures [20 ▪▪ ]. If the tight interaction of macrophages with other cell types in the islands limit the number or bias the populations of the central macrophages isolated for further studies, perhaps we must isolate deeper structures within the cell, such as the nucleus or mitochondria, for the unique cellular signature that is so important for understanding the EMBI [41].…”
Section: Discussionmentioning
confidence: 99%
“…[12] suggested that myeloid cells were also found in close association with the central macrophage in the islands isolated from the rabbit bone marrow. We knew very recently that EBIs not only support erythroid precursors, but neutrophil precursors as well, expanding our understanding of the niche and proposing renaming it to an erythromyeloblastic island (EMBI) [20 ▪▪ ].…”
Section: Redefining the Concept Of The Erythoblastic Niche Into An Er...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Blood, Romano et al discover that in murine bone marrow, both granulocyte and erythroid precursors develop around a single central macrophage, within a specialized niche termed erythromyeloblastic islands (EMBI). 1 Although it is well established that mammalian erythropoiesis occurs in erythroblastic islands (EBI), comprising 5 to 30 maturing red blood cell precursors surrounding a macrophage, 2 like an orchestra around a conductor, Romano et al identify that the "orchestra" constitutes granulocyte as well as erythroid precursors. Furthermore, they introduce a new concept in hematopoietic cell homeostasis: an inverse relationship between erythroid and granulocyte lineage cell numbers in EMBI that vary in response to microenvironmental cues.…”
Section: Deena Iskander | Imperial College Londonmentioning
confidence: 99%
“…In this issue of Blood, Albert et al 1 present compelling evidence that allogeneic hematopoietic stem cell transplantation (HSCT) is a highly feasible and potentially curative approach for adults with inborn errors of immunity (IEI).…”
Section: Transplantationmentioning
confidence: 99%